The Study of Folk Music in the Modern World - Bohlman, Philip V. (Indiana University Press, 1988)
Bohlman examines folk music as a genre of folklore from a broadly cross-cultural perspective. His study espouses a more expansive view of folk music, a view stressing the vitality of folk music in non-Western cultures as well as Western, in the present as well as the past. A wide range of examples-especially from the Middle East and American ethnic communities-illustrates the sheer richness of folk music in the twentieth century. A reconsideration of the folk musician as an agent of creativity underscores the book's assertion that folk music is not a disappearing genre, but rather an expressive behavior intrinsically part of the modern world.